3 - Ajustement structurel et désengagement de l’Etat en Côte d’Ivoire: by Echimane Mozou Vincent & Niamkey Amlan Madele - Echimane Mozou Vincent; Niamkey Amlan Madele (Africa Development, 1988)
Structural Adjustment programmes devised by the IMF and World Bank and implemented in developing countries have failed because the major theoretical assumptions in forming these programmes are false. In general, they have resulted in the deterioration of the standard of living of the population, regression of economic activities, social upheavals and an unbeatable debt burden. In the case of Côte d'Ivoire, the IMF notion of disequilibria does not reflect the nature of the existing supply and demand. The prescribed restrictive monetary and budgetary measures tend to aggravate the crisis. Contrary to the IMF solutions, alternative measures can be adopted to solve the problem in the balance of payment and budget deficit i.e. cutting imports of inessential products, equal resource inputs to the food and export sector in agriculture. Disengagement of the state from the economy, privatization and an open market will not eliminate the existing disequibrium. On the contrary, the economic role of the state needs to be reinforced and public enterprises must be reformed. Economic development should be primarily based on the mobilization of internal resources. The restructuration of the economy of developing countries will be of little use without a concomitant opening and favorable re structuration of the developed countries